Section bending resistance of new Hybrid Double-I-Box Beams. Issue 11 (August 2018) - Deepak, MS; Shanthi, VM
This article contains original works of testing and numerical validation on section bending resistance of new innovative built-up thin-walled metal Hybrid Double-I-Box Beam sections when subjected to local buckling. The cross section of Hybrid Double-I-Box Beam section is distinctive, which has advantages of both an 'I' section and a closed-box section. A total of 24 sections in three series that includes 8 homogeneous sections and 16 hybrid sections were tested under four-point bending. The varying parameters considered in the test specimens were as follows: first, hybrid parameter ratio, that is, yield strengths of flange steel to web steel (Φh = fyf /fyw ); second, the ratio of breadth to the overall depth (B/D) of the section; and third, the flange thickness (tf ). The moment-resisting capacity of these built-up sections are high due to the presence of more material at the flanges. The closed box-web portion provides higher torsional rigidity. From the test results, it was found that the hybrid sections have higher bending resistance capacity than the homogeneous sections, so technically gains more strength to weight. The increase in B/D ratio gained the increase in both major and minor axis bending resistance. The intermediate flange stiffener which alters the flange plate slenderness (λpf ) had a significant effect on the local buckling resistance of the flange plate. Verification of numerical models followed by a parametric study was undertaken using ABAQUS finite element analysis software. The test results obtained were compared with the predicted design moment of resistance (Mc, Rd ) as per Eurocode design standards EN 1993-1-3: 2006-Design of Steel Structures for Cold-Formed Steel Members and Sheeting and the adequacy is confirmed.